A Novel Technique for Conjunctivoplasty in a Rabbit Model: Platelet-Rich Fibrin Membrane Grafting. (22nd September 2016) - Can, Mehmet Erol; Çakmak, Hasan Basri; Dereli Can, Gamze; Ünverdi, Hatice; Toklu, Yasin; Hücemenoğlu, Sema
Abstract : Purpose . To investigate the effect of platelet-rich fibrin (PRF) membrane on wound healing. Methods . Twenty-four right eyes of 24 New Zealand rabbits equally divided into 2 groups for the study design. After the creation of 5 × 5 mm conjunctival damage, it was secured with PRF membrane, which was generated from the rabbit's whole blood samples in PRF membrane group, whereas damage was left unsutured in the control group. Three animals were sacrificed in each group on the 1st, 3rd, 7th, and 28th postoperative days. Immunohistochemical (IHC) stainings and biomicroscopic evaluation were performed and compared between groups. Results . PRF membrane generated significant expressions of vascular endothelial growth factor (VEGF), transforming growth factor-beta (TGF-β ), and platelet-derived growth factor (PDGF) in the early postoperative period. However, the IHC evaluation allowed showing the excessive staining at day 28, in control group. Biomicroscopic evaluation revealed complete epithelialization in PRF membrane group, but none of the cases showed complete healing in the control group. Conclusions . This experimental study showed us the beneficial effects of the PRF membrane on conjunctival healing. Besides its chemical effects, it provides mechanical support as a scaffold for the migrating cells that are important for ocular surface regeneration. These overall results encourage us to apply autologous PRF membrane as a growth factor-enriched endogenous scaffold for ocular surface reconstruction.